Finance and Development, September 1971. (Finance and Development; Finance and Development, 1971)
This paper focuses on currency convertibility and the exchange rate system. The paper explains some of the factors involved in extending the freedom of currency convertibility, one of the IMF's principal policy aims. It highlights that the IMF's Articles of Agreement make the distinction between currency convertibility for residents and for nonresidents, but make it an obligation in principle to avoid restrictions on current payments of both categories. The paper also discusses management in developing countries as well as the link between growth and structural change.